2020
DOI: 10.3389/fchem.2020.00657
|View full text |Cite
|
Sign up to set email alerts
|

High Triplet Energy Host Materials for Blue TADF OLEDs—A Tool Box Approach

Abstract: The synthesis of stable blue TADF emitters and the corresponding matrix materials is one of the biggest challenges in the development of novel OLED materials. We present six bipolar host materials based on triazine as an acceptor and two types of donors, namely, carbazole, and acridine. Using a tool box approach, the chemical structure of the materials is changed in a systematic way. Both the carbazole and acridine donor are connected to the triazine acceptor via a para-or a meta-linked phenyl ring or are link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…However, despite the logical implications for triplet energies and how these determine host/guest compatibility, it is not commonplace to report neat film phosphorescence of new OLED host materials. Instead, low temperature solution measurements currently dominate the literature in reports of this kind [69, 76–87] . A recent study by Forrest and Thompson [73] has demonstrated that such solution measurements do not give appropriate triplet energies for the design of OLEDs, while the results here show that phosphorescence in dilute polymer films is also not suitable in this regard.…”
Section: Resultsmentioning
confidence: 72%
“…However, despite the logical implications for triplet energies and how these determine host/guest compatibility, it is not commonplace to report neat film phosphorescence of new OLED host materials. Instead, low temperature solution measurements currently dominate the literature in reports of this kind [69, 76–87] . A recent study by Forrest and Thompson [73] has demonstrated that such solution measurements do not give appropriate triplet energies for the design of OLEDs, while the results here show that phosphorescence in dilute polymer films is also not suitable in this regard.…”
Section: Resultsmentioning
confidence: 72%
“…For this purpose, three novel host molecules were designed. As presented in previous work, 34 by direct connection of donors (acridine and carbazole) and acceptors (triazine), it is possible to increase the triplet energy of donor-acceptor molecules compared to the case where the connection occurs via a conjugated bridge. In this work, acridine (donor) and three different pyrimidines (acceptors) with a different size of the conjugated system of the pyrimidine were chosen to obtain three materials of different conjugation.…”
Section: Design and Synthesismentioning
confidence: 90%
“…This implies that for PXZ-based molecules, there are two LE triplet states that are very close in energy. This is not the case for DMAC-based molecules, where donor triplet state has an energy of around 3.1 Ev (Rodella et al, 2020). The relative position of these lowest triplet states can vary, depending on the host properties.…”
Section: Luminescence In Blend Mcp Filmsmentioning
confidence: 97%
“…Taking into account the structureless absorption spectra of the donors, one can assign these maxima to localized ππ * transitions of the acceptor OBO moiety (Numano et al, 2016). In the case of DMAC molecules, the absorption of the donor is masked by absorption of the acceptor and cannot be clearly observed (Rodella et al, 2020). In contrast, for the PXZ compounds, the contribution of the donor is distinguished as the shoulder at 350 nm (Mantsch, 1969).…”
Section: Absorption and Emission In Solutionsmentioning
confidence: 99%